2013
DOI: 10.1097/jto.0b013e318282ded5
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Study of Cetuximab and Bevacizumab in Combination with Two Regimens of Paclitaxel and Carboplatin in Chemonaive Patients with Stage IIIB/IV Non–Small-Cell Lung Cancer

Abstract: Both the regimens showed expected PFS and numerically comparable overall survival. Quality of life was similar in the two arms, and both the regimens were well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Bevacizumab, a humanized mAb directed against vascular endothelial growth factor (VEGF), was the first angiogenesis inhibitor approved for first-line treatment of patients with non-squamous NSCLC based on data from two studies that demonstrated ∼ 2 months of improvements in PFS and an improvement in OS, with results later replicated in Chinese patients with non-squamous NSCLC [ 53–55 ]. In a randomized phase II trial, cetuximab plus bevacizumab for the treatment of chemotherapy-naïve patients with advanced non-squamous NSCLC showed a prolonged median PFS of 6.05 months when combined with six cycles of chemotherapy [ 56 ]. It is important to note, however, that bevacizumab is contraindicated for treatment of patients with SqCLC due to a heightened risk of life-threatening pulmonary hemorrhage in this patient population [ 3 , 57 ].…”
Section: Egfr-directed Mabs In Combination With Antiangiogenic Agentsmentioning
confidence: 99%
“…Bevacizumab, a humanized mAb directed against vascular endothelial growth factor (VEGF), was the first angiogenesis inhibitor approved for first-line treatment of patients with non-squamous NSCLC based on data from two studies that demonstrated ∼ 2 months of improvements in PFS and an improvement in OS, with results later replicated in Chinese patients with non-squamous NSCLC [ 53–55 ]. In a randomized phase II trial, cetuximab plus bevacizumab for the treatment of chemotherapy-naïve patients with advanced non-squamous NSCLC showed a prolonged median PFS of 6.05 months when combined with six cycles of chemotherapy [ 56 ]. It is important to note, however, that bevacizumab is contraindicated for treatment of patients with SqCLC due to a heightened risk of life-threatening pulmonary hemorrhage in this patient population [ 3 , 57 ].…”
Section: Egfr-directed Mabs In Combination With Antiangiogenic Agentsmentioning
confidence: 99%
“…Studies have also examined cetuximab treatment for non-small cell lung cancer (NSCLC), breast cancer, and hepatocellular carcinoma (HCC). 57…”
Section: Introductionmentioning
confidence: 99%
“…Bevacizumab binds to VEGF and prevents the proliferation of endothelial cells and formation of blood vessels, as well as decreases the blood supply and reduces tumor interstitial pressure. Thus, the ability of chemotherapy to reach the tumor is increased by the combinatorial treatment 20,7073…”
Section: Supporting Treatment With Monoclonal Antibodiesmentioning
confidence: 99%